CHARACTERISTICS OF THE DEVELOPMENT OF PHYSICAL EDUCATION IN THE ANCIENT EAST, ANCIENT GREECE, ANCIENT ROME - Oybek Parpiev (Journal Park Publishing, 2023)
Physical education is a type of education, the uniqueness of its content reflects the teaching of movement exercises, the formation of physical qualities, the acquisition of special physical education knowledge and the formation of a conscious need to engage in physical education. The system of physical education is a historically conditional type of social practice of physical education, which includes the worldview, scientific-methodical, program-normative and organizational foundations that ensure the physical maturity of people. In the article, the concept of physical education and its content, as well as the characteristics of the development of physical education in the ancient East, ancient Greece, and ancient Rome are scientifically researched.
Keywords: physical education, physical education in the ancient East, physical education in ancient Greece, physical education in ancient Rome.